Intelligence and consciousness in the machinic extensions of the human body - Hildebrand, Hermes Renato; Sogabe, Milton Terumitsu; Fogliano, Fernando Luiz; Blumenschein, Julia Camille; Leote, Rosangela da Silva [UNESP]; ACM; Arantes, P.; Sa, V. J.; DaVeiga, P. A.; Fernandes-Marcos, A. (Assoc Computing Machinery, 2019)
The questioning about intelligence and consciousness in machines is discussed here, departing from the observation of the human body extensions used to amplify the human potential. Therefore, we approach types of machinic extensions, understood as muscular, sensory and cerebral, and going to the concepts of intelligence and artificial awareness. In this context, the use of such technologies in the creative construction of Art is presented, including Generative Art. It is intended that the debate about the possibility that, in the future, machines will be able to create and thus be considered conscious and intelligent.
Keywords: Artificial Intelligence; Consciousness; Body Extensions; Generative Art